Mitigating bad debt risk through the implementation of risk management at the Regional Bank of North Sumatra - Nurhaflah Soraya; Khairi Anshor (Institute of Computer Science (IOCS), 2024)
Bank operational activities have a significant impact on the economy and therefore require regulations that can minimise potential risks that may occur. The purpose of this study is to review the implementation of risk management in depth at the Regional Bank of North Sumatra. This study uses secondary data from annual reports published during 2018-2022. This research is a descriptive research that will be described through data on credit risk, risk management and bad debts. The results of this study indicate that the Regional Bank of North Sumatra has successfully implemented risk management well even though there are some limitations in the process.